Bone mineral content distribution in response to long-term training of elite rowers - Mourtakos, S.; Kavouras, S.; Vasiliou, S.; Soultanakis, H.; Bardis, C.; Sidossis, L.; Tenta, R. (In vivo : international journal of experimental and clinical pathophysiology and drug research, 2022)
Background/Aim: Bone response to exercise depends on the type and size of the mechanical stimulus. In rowing, athletes are exposed to low mechanical but large compression loads mainly on the trunk. Thus, this study aimed to investigate the impact of rowing on total and regional bone quality and bone turnover parameters in elite rowing athletes vs. control subjects.